Career Counseling and Student-Athletes: A Needs Assessment - Etzel, Edward F.; Barrow, John C.; Pinkney, James W. (My University, 1994)
The self-reported personal/social needs of a random sample of 170 college student-athletes and a general student sample (n=300) at a Division I institution were compared. The authors used a needs assessment survey with 54 Likert items modified from an instrument by Talley (1985) and 14 additional items about athletic competition and counseling services. Usable surveys returned were 201 total from both groups. Survey data revelated that both groups shared many needs. Respondents indicated that career-related concerns and various sources of stress associated with participation in athletics were of primary concern. Findings provide suggestions for the planning and delivery of helping services to student-athletes and non-athletes.
Keywords: academic support; career development